Airfoil Aerodynamics in Proximity to Wavy Ground for a Wide Range of Angles of Attack - Haode Hu; Dongli Ma (Applied Sciences, 2020)
Wing-in-ground craft often encounter waves when flying over the sea surface, and the ground effect is more complicated than that of flat ground. Therefore, the aerodynamic characteristics of the NACA 4412 airfoil in proximity to wavy ground for a wide range of angles of attack is studied by solving the Reynolds Averaged Navier–Stokes equations. The validation of the numerical method is carried out by comparing it with the experimental data. The results show that the aerodynamic coefficients will fluctuate periodically when the airfoil moves over wavy ground at a small ride height. Except for the angle of attack of 0°, the fluctuation trend of aerodynamic coefficients at other angles of attack is the same. The analysis of aerodynamic fluctuation amplitude found that the medium angle of attack should be selected as the design cruise angle of attack for wing-in-ground craft. The time-averaged aerodynamic coefficients in the case of wavy ground are almost the same as those of flat ground. Hence, wavy ground mainly causes a fluctuation in aerodynamic coefficients. Considering the difference between aerodynamic coefficients at the angle of attack of 0° and at other angles of attack, the flow field structure at an angle of attack of 0° and 4° is analyzed. The results reveal the aerodynamic characteristics of the airfoil moving over wavy ground, which gives a deeper understanding of the ground effect in the conditions of wavy surface/ground. This has a certain guiding significance for the design of wing-in-ground craft.